2011
DOI: 10.1542/peds.2011-0961
|View full text |Cite
|
Sign up to set email alerts
|

Child Marriage in the United States and Its Association With Mental Health in Women

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The prevalence of child marriage (marriage at Ͻ18 years of age) in Western countries is considered to be low. Although child marriage has a devastating impact on health, no study has yet evaluated the impact of child marriage on mental health. WHAT THIS STUDY ADDS:The prevalence of child marriage among women in the United States was 8.9%. Child marriage was associated with higher rates of lifetime and 12-month psychiatric disorders. In addition, women who married as children were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 13 publications
4
94
1
10
Order By: Relevance
“…Results of studies have confirmed that because girls do not mature physically at an early age, married people can get the physical problems and mood disorders depression anxiety disorders and obsessive and make dismay [5]. Iron and calcium deficiency is very common in girls under 18 years of age and pregnancy on the risk of osteoporosis and anaemia in them increases [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…Results of studies have confirmed that because girls do not mature physically at an early age, married people can get the physical problems and mood disorders depression anxiety disorders and obsessive and make dismay [5]. Iron and calcium deficiency is very common in girls under 18 years of age and pregnancy on the risk of osteoporosis and anaemia in them increases [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…In reality, protection from violence is not guaranteed, and physical and sexual violence is often experienced at the hands of the husband once the marriage has occurred (Plan UK 2011). Child brides also suffer emotional violence in their homes and experience severe isolation and depression as a result of early marriage (Le Strat, Dubertret, & Le Foll 2011;Nour 2009). Indeed, girls who are married early are at a higher risk of experiencing intimate partner violence (IPV) than girls married after age 18 (Clark, Bruce, & Dude 2006).…”
Section: Violencementioning
confidence: 99%
“…Küçük yaþta yapýlan evliliklerde kadýnlarda ruhsal hastalýk ve psikiyatrik destek arama oranýnýn yetiþkin yaþta evlenen kadýnlara göre daha fazla oranda görüldüðü belirtilmiþtir (9). Ülkemizde erken yaþta evlenen kýzlarla yapýlan çalýþmada da bu çocuklarýn %45.8'inde en az bir psikiyatrik bozukluk olduðu gösterilmiþtir (3).…”
Section: Gýrýþunclassified
“…Erken yaþta evlenen bu çocuklarda psikiyatrik bozukluk oranlarýnýn yüksek olduðu gösterilmiþ (9) ve çocuk evliliklerinin ergenlerde artmýþ intihar riski ile iliþkili olduðu belirtilmiþtir (24). Ülkemizde erken evlendirilen çocuklarla yapýlan çalýþmalarda ruhsal bozukluk oranlarý %45.8 ve %46.2 olduðu belirtilmiþtir (3,25).…”
Section: Tartiþmaunclassified